Peritoneal Dialysis-Related Peritonitis: Rate, Clinical Outcomes and Patient Survival - Dzekova Vidimliski, Pavlina; Nikolov, Igor; Gjorgjievski, Nikola; Selim Gjulsen; Trajcheska, Lada; Stojanoska, Ana; Rambabova Bushljetik, Irena; Simeonov, Risto; Stojkovski, Ljupco (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2021)
Peritoneal dialysis-related peritonitis remains the major complication and primary challenge to the long-term success of peritoneal dialysis (PD). The study aimed to analyze the peritonitis rate, the cause, the outcomes, and the association of peritonitis with the survival of patients on peritoneal dialysis. Patient data were collected retrospectively from medical charts. A total of 96 patients received peritoneal dialysis in the PD center from 1 January 1999 to 31 December 2018. Episodes of peritonitis (n=159) were registered in 54 (56.3%) patients. The study population was divided into two groups, a group of patients (n=54) who experienced peritonitis and a group of patients free of peritonitis (n=42). The peritonitis rate was 0.47 episodes per patient year. The majority of causative microorganisms were gram-positive bacteria (53.5%). Outcomes of the episodes of peritonitis were resolved infection in 84.9% of episodes, catheter removal in 11.3% of episodes, and death in 3.8% of the episodes of peritonitis. A Kaplan–Meier analysis and log-rank test revealed that the group with peritonitis tended to survive significantly longer than the peritonitis-free group. A 67% reduction rate in the risk of patient mortality was observed for the peritonitis group compared with the peritonitis-free group (hazard ratio: 0.33, 95% CI 0.19-0.57, P=0.000). The prevention and management of PD-related infections, resulted in their worldwide reduction, supporting the use of PD as a first-line dialysis modality.